Anxious immobilities: an ethnography of coping with contagion (Covid-19) in Macau - Zuev, Dennis; Hannam, Kevin (Mobilities, 2020)
In February 2020, Macau became one of the first regions where the pandemic of coronavirus or Covid-19 affected the totality of social and economic life leading to increased anxieties over movement and distance. Although Macau has had very few actual cases of the virus – 46 in total –and no deaths from it, the Macau government rapidly instituted a lock down. The aim of this article is to reflect on how the social experience of being in lockdown can provide insights into understanding the type of experience or condition that we provisionally term ‘anxious immobility.’ Such a condition is characterized by a total disruption of everyday rhythms and specifically anxious waiting for the normalization of activity while being the subject of biosocial narratives of quarantine and socially responsible. The paper is based upon 3 months of ethnographic research conducted by two researchers based in Macau. We also reflect upon some aspects of the politics of mobilities in the light of disruptions and friction points between Hong Kong, Macau, mainland China, and the rest of the world.

A touristic habitation: automobilities of Chinese driving tourists - Yang, Peng; Xu, Honggang; Hannam, Kevin (Tourism Geographies, 2022)
As an emergent tourism sector, driving tourism connects car use and touristic activities intimately. Following the notion of the ‘inhabited car’, this article explores how and why Chinese tourists inhabit a travelling car for drivers/passengers in the leisure automobility and driving tourism context. Through three different road trips and ‘mobile methods’, it was found that Chinese tourists inhabit the car in four ways: driving, gazing, listening, and communicating. Through this embodied habitation, the car is turned into a ‘touristic inhabitation’ space for protecting the tourists generating touristic emotions、social interactions, and tourism meanings. The study contributes to automobility and tourism literature and provides implications for driving tourism development in China.
Keywords: Automobilities; China; cars; driving tourism; habitation

A network analysis investigation of the comorbidity between sleep dysfunction and PTSD symptomatology among Filipino domestic workers in Macao (SAR) China- ClinicalKey - Wang, Siyuan; Sit, Hao Fong; Garabiles, Melissa R.; Blum, Daniel; Hannam, Kevin; Armour, Chérie; Hall, Brian J. (Journal of Psychiatric Research, 2021)

Acculturative stress and coping among migrant workers: A global mixed-methods systematic review - Liem, Andrian; Renzaho, Andre M. N.; Hannam, Kevin; Lam, Agnes I. F.; Hall, Brian J. (Applied Psychology: Health and Well-Being, 2021)
No existing review has synthesized key questions about acculturation experiences among international migrant workers. This review aimed to explore (1) What are global migrant workers’ experiences with acculturation and acculturative stress? (2) What are acculturative stress coping strategies used by migrant workers? And (3) how effective are these strategies for migrant workers in assisting their acculturation in the host countries? Peer-reviewed and gray literature, without time limitation, were searched in six databases and included if the study: focused on acculturative stress and coping strategies; was conducted with international migrant workers; was published in English; and was empirical. Eleven studies met the inclusion criteria. Three-layered themes of acculturation process and acculturative stress were identified as: individual layer; work-related layer; and social layer. Three key coping strategies were identified: emotion-focused; problem-focused; and appraisal-focused. These coping strategies were used flexibly to increase coping effectiveness and evidence emerged that a particular type of acculturative stress might be solved more effectively by a specific coping strategy. Migrant workers faced numerous challenges in their acculturative process. Understanding this process and their coping strategies could be used in developing research and interventions to improve the well-being of migrant workers.
Keywords: acculturation; cultural adaptation; global mental health; health disparities; healthcare access; migrant health

Tourist’s mobilities: Walking, cycling, driving and waiting - Hannam, Kevin; Butler, Gareth; Witte, Alexandra; Zuev, Dennis (Tourist Studies, 2021)
This commentary reviews recent research in terms of tourist’s mobilities in terms practices of walking, cycling and driving. It concludes by reflecting on the contemporary lock down of travel in terms of the global pandemic and its consequences for waiting, stillness and immobility – particularly in terms of flying.

Pandemic (Im)mobilities - Adey, Peter; Hannam, Kevin; Sheller, Mimi; Tyfield, David (Mobilities, 2021)